Flood and riverbank erosion displaces: their indigenous survival strategies in two coastal villages in Bangladesh - Karim, A.H.M Zehadul (Canadian Center of Science and Education, 2014)
It is reported that flood and riverbank erosion together intensify the process of pauperization in rural areas of Bangladesh. Riverbank erosion often destroys cultivable land, dislocates human settlements and also at the same time, damages the growing crops; massively disrupts road-linkages and communication infrastructure in the country. With this situation, this paper generates empirical data on two coastal villages located in two different regions of the country showing evidence of displacement of the total way of life due to flood and riverbank erosion. Due to this natural calamity, the victims have to adapt to the changing environmental conditions, and consequently they adopt many socio-political, economic and cultural strategies in order to survive in the face of the plethora of problems. Flood and river bank erosion displacees try to gain control over their environment through their multi-dimensional adaptation strategies. This paper thus locates the indigenous strategies and mechanisms that the displacees usually adopt to grapple with the catastrophic effects of flood and erosion in the coastal areas of rural Bangladesh.